Metabolites from lactococcus lactis subsp. lactis: isolation, structure elucidation, and antimicrobial activity - Navale, Vishwambar D.; Borade, Balasaheb R.; Rama Krishna, Gamidi; Vamkudoth, Koteswara Rao; Kontham, Ravindar (ACS Omega, 2023)
Herein, we disclose the identification of novel metabolites from a potential probiotic strain, Lactococcus lactis subsp. lactis, obtained from traditional dairy milk samples collected in Maharashtra, India (in January 2021). Isolated metabolites include pyrazin-2-carboxamide [1, pyrazinamide, a potential antitubercular drug], 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one (2, DDMP), 2,4-di-tert-butylphenol (3), and hexadecanoic acid (4, palmitic acid). The chemical structures of these metabolites were elucidated through extensive 1D NMR (H-1 and C-13) and 2D NMR (HSQC, HMBC, and NOESY) analyses, high-resolution mass spectrometry, high-performance liquid chromatography, and single-crystal X-ray crystallography. Furthermore, these novel metabolites exhibited potent inhibitory activities against various bacteria, fungi, and yeast strains with minimum inhibitory concentrations ranging between 1.56 and 25 mu g/mL, and compounds 1 and 3 were found to be most active against a wide range of microbial strains tested.